Farmers' background and diversity of uses of palm oil wastes for sustainable agriculture in Southern Benin Republic - KOURA, Tatiana W.; DAGBENONBAKIN, Gustave D.; KINDOMIHOU, M. VALENTIN; SINSIN, Brice (My University, 2015)
Palm oil mill wastes (POMW) are well known to be rich in phosphorus, nitrogen, calcium, magnesium, sodium and potassium. This study was carried out in 2012 to assess farmers‟ practices on utilization of POMW in agriculture in the south of Benin. A total of 335 palm oil mills from the Communal Union of Palm Oil Producers were randomly selected and surveyed using a questionnaire. The use of POMW as fertilizers depends highly ( p , 0.001) on the nature of fertilizers used by the farmer. The use of empty fruit bunches (EFB) and fibre as fertilizers depends on the knowledge of the farmer about their application directly in palm plantations or indirectly through composting. These wastes were applied by local application (76.5%) or mulching (33.3%). The use of EFB and fibre produced depends on their use in plantations ( p , 0.001). POMW were composted by heaping, by breeding pigs on POMW and in pits. Breeding pigs on POMW involved placing POMW in a pig pen with added vegetables. The pit method consisted of making a hole. The POMW are put in the pit. After the short rain season, the compost obtained can be used. Composting is a process unknown by 67.5% of mill owners. The difference between those who know about and use composting, and those who know it but do not use it is based on their knowledge of composting advantages. The use of POMW in composting is mostly developed in Ifangni District (Plateau Department).
Keywords: Composting; Knowledge; Palm oil mill waste